Providing perinatal loss care: Satisfying and dissatisfying aspects for midwives - Fenwick, Jennifer; Jennings, B.; Downie, Jill; Butt, Janice; Okanaga, M. (Elsevier, 2007)
There is limited midwifery research that focuses on midwives experiences and attitudes to providing care for women who experience the death of a baby. There is also limited research investigating care components, and evidence to inform the basis of clinical practice in Austtralia and internationally. This paper presents the qualitative findings of a small study that aimed to investigate midwives experience, confidence and satisfaction with providing care for women who experienced perinatal loss. Procedure: Eighty-three Western Australian midwives responded to an open ended question asking them to describe the most and least satisfying aaspects of their role when providing care to women who experienced a perinatal loss. Thematic analysis was used to analyse the data. Findings: The analysis revealed that Australian midwives gained most satisfaction from providing skilled midwifery care that they considered made a difference to women. This was enabled when midwives were afforded the opportunity to provide continuity of midwifery carer to women throughout the labour, birth and early postnatal period. In terms of the least satisfying aspects of care, midwives identified that they struggled with the emoptional commitment needed to provide perinatal loss care, as well as with how to communicate openly and share information with women. Conclusions and implications for practice: Within the context of the study setting, midwifery care for women following perinatal loss reflects the care components espoused in the literature. There are however, organisational issues within health care that require commitment to continuity of care and further education of practioners to enhance outcomes for clients.